1068 QIP ASSESSING ROUTINE RECORDING OF OVERNIGHT VITAL SIGNS (OVS) AND OVERNIGHT MEDICATIONS ADMINISTRATIONS (OMARS) IN ELDERLY CARE. (14th June 2022) - Rizvi, S; McNeela, N; Masood, I; Akinlade, O; Ajaja, O; Cole, M
Abstract: Introduction: Poor sleep is experienced by up to half of hospital inpatients1, associated with poor cognition, weak immunity, hypertension and increased mortality2. Recent studies recommend fewer sleep interruptions through targeted reductions in routine recording of overnight vital signs (OVS) and overnight medication administrations (OMARS) 3. The following standards were agreed at New Cross Hospital for audit (expected compliance 90%); 1. Routine OVS for stable patients shouldn't be done overnight (2, 200 pm to 0600 am). 2. Routine OMARS shouldn't be undertaken overnight. These were derived after scrutinizing following; NICE CG1034 and QS635, NSF (Department of health)-4.256, RCP Acute care toolkit 37, CG508. Method: Retrospective data recorded over 10 days in May and August 2021 from electronic records which included 61 elderly patients in 1st and 53 in 2nd audit cycle. Exclusion was Early Warning Score ≥ 3. We also ran night shift surveys to observe staff perceptions, completed online. Results: OVS recording showed poor compliance of 0% and 3.77%. OMARS were done in less than half of patients but improved in subsequent audit cycle to about in 1/3rd of patients (77.35% compliance). No patient became unwell or required escalation of care. The estimated time spent on these interventions was 2.5 hours/week or 30 days in 1 calendar year. Almost all survey participants agreed to stop OVS while 66.6% of them agreed to stop OMARS in both cycles. 39.39% in 1st cycle believed that this strategy can cause harm and this misperception was reduced to 22.22% in subsequent cycle. Conclusion: Our QIP advocates for rationalizing interventions and ensuring we only complete interventions where clinically relevant9. It showed improvement in reducing OMARS but success in stopping OVS couldn't be fully translated in true spirits, possibly due to common misperceptions which will be further addressed in subsequent audit cycles.